Hybrid Model Restorative Justice Komparatif Antara Sistem Civil Law dan Common Law (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the Hybrid Model of Restorative Justice from a comparative perspective between Civil Law and Common Law systems as a reflection of the transformation of criminal law policy. The Civil Law system, rooted in legal positivism, emphasizes formal legal certainty through codification, whereas the Common Law system allows broader judicial discretion and judge-made law. These differing paradigms significantly influence the development and implementation of restorative justice. Indonesia, as a Civil Law country, has demonstrated a shift toward a hybrid legal policy by incorporating Common Law values into its criminal justice reforms, particularly through the National Criminal Code. This research employs a normative juridical method using conceptual, statutory, and comparative law approaches. The findings indicate that the Hybrid Model of Restorative Justice represents a strategic legal policy choice aimed at harmonizing legal certainty and substantive justice in accordance with the Pancasila legal ideals.